The Opportunities of the Inter-Municipal Strategic Alliances in Algeria (Global Journal of Human-Social Science, 2016)
The purpose of this contribution is to assess the opportunity of inter-municipal strategic alliances in Algeria It aims at providing a precise answer to the question whether the inter-municipal strategic alliances are an efficient tool to reduce or even eliminate the inconsistencies in the current territorial division in Algeria This paper presents the results of a survey administered via a questionnaire drawn from the theoretical foundations of strategic alliances The questionnaire then is divided in two sections The first section provides a profile of respondents and develops methodological elements mobilized in the investigation The second section gives details about the main results
Keywords: strategic alliances; algeria; sustainability